How is the Muscle and Cardiovascular Endurance Level of Players In The Patalassang Football Association (PERSEPAT FC) - hasmyati, Hasmyati; Atifa Anwar, Nur Indah (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of muscle and cardiovascular endurance of Patalassang Football Association (PERSEPAT FC) players. The method used in this study is a survey with data analysis techniques using SPSS 21. The research sample consisted of 10 PERSEPAT FC players. The results of the analysis showed that the level of muscle endurance of PERSEPAT FC players based on Table 4. 3 had the following distribution: 2 people (20%) were in a good category, and 8 people (80%) were in the fair category. Meanwhile, the results of the analysis of cardiovascular endurance levels based on Table 4.4 show that 2 people (20%) are in the very poor category, and 8 people (80%) are in the poor category. These findings indicate that the majority of players have a sufficient level of muscle endurance, but cardiovascular endurance is still relatively low. Therefore, a more focused training program on improving cardiovascular endurance is needed to improve players' physical performance.